Immunohistological analysis of tumour growth factor beta 1 expression in normal and inflamed salivary glands. Issue 9 (September 1996) - Kizu, Y; Sakurai, H; Katagiri, S; Shinozaki, N; Ono, M; Tsubota, K; Saito, J
Abstract : AIM: To determine whether transforming growth factor-beta 1 (TGF-beta 1) has a pathogenetic role in disease of the salivary glands. METHODS: An indirect immunohistochemical technique was used to analyse TGF-beta 1 expression in six specimens of normal salivary gland and 23 surgical specimens. RESULTS: TGF-beta 1 was strongly expressed in the ductal epithelial cells of normal salivary gland tissues (six of six cases) and in inflammatory conditions (eight of 11 cases). In contrast, TGF-beta 1 was not detectable in ductal epithelial cells expressing HLA-DR around infiltrating CD4+ CD45RO+ activated T cells, in the salivary gland tissue of patients with Sjögren's syndrome. CONCLUSION: Because TGF-beta 1 has an essential role in the mucosal immunity of salivary glands, abnormal expression of this cytokine must be regarded as a candidate in the pathogenesis of Sjögren's syndrome.